Sensory characteristics and factors influencing consumers’ preferences towards goat milk in peninsular Malaysia - Ismail., Alia Khalidah (2021)
Goat milk provides a healthy diet, which is essential for the proper development of your body, packaged with calcium, carbohydrates, fats, minerals, and vitamins that contribute to the growing demand for milk and milk products. Furthermore, milk consumption rises year-round due to health claims to prevent any disease. However, Malaysians consume a low amount of milk and milk products for recommended dietary intake, especially from source of goat milk. The situation is due to human attitudes, food neophobia, and poor eating habits among Malaysians. Thus, the general objective of the conducted study was to determine sensory characteristics and factors influencing consumers’ preferences towards goat milk in Peninsular Malaysia. Meanwhile, the specific objectives of the study were to determine the sensory characteristics of different samples of goat milk; to determine the association between socio-demographic characteristic and consumer preferences for goat milk; to determine the factor affecting consumer preferences for goat milk; and to identify the most influential factors that influence consumers’ preference for goat milk. Purposive sampling was used to select 649 goat milk consumers to represent Peninsular Malaysia. Primary data was conducted at the Malaysia Agriculture, Horticulture and Agrotourism (MAHA) 2018 as Central Location Test (CLT). The data was gathered using a structured survey. Four samples of goat milk that were purchased from a supermarket and a local farmer was used for sensory evaluation: two samples from the supermarket and two samples from the farmer. Data were analysed using descriptive analysis, analysis of variance (one-way ANOVA), Chi-square analysis, factor analysis and binary logistic regression analysis.